PUBLIC-PRIVATE PARTNERSHIP – AS A TOOL FOR SOLVING ENVIRONMENTAL PROBLEMS - Arynova Zulfiya Amangeldykyzy; Rakhmetullina Shynar Zhakanovna (Academic Journal of Physical and Chemical Sciences, 2020)
Without using the PPP mechanism, it is impossible to solve one of the most acute problems that cause the keen attention of citizens of the country. Given the budget deficit, the introduction of a public-private partnership mechanism and an efficient system of using resource-saving technologies will contribute to solving environmental problems, in particular, eliminating accumulated environmental damage, improving air quality and optimizing the waste management system. Given the budget deficit, the introduction of a public-private partnership mechanism and an efficient system of using resource-saving technologies will contribute to solving environmental problems, in particular, eliminating accumulated environmental damage, improving air quality and optimizing the waste management system. There are listed spheres and sectors of application of public private partnership. There are mentioned advantages of the use of public private partnership. The statistical data and the dynamics of implementation of projects implemented on the basis of public private partnership are presented. An example of the use of public private partnership as an instrument for the development of territories is presented. Attention is paid to the institutional environment of the implementation of public private partnership projects.